Pelaksanaan Pembelajaran Keterampilan Menulis Teks Eksplanasi pada Siswa Kelas XI SMA Negeri 2 Rejang Lebong - Putriani, Ayu; Noermanzah, Noermanzah; Yulistio, Didi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
The skill of writing explanatory text is part of the Indonesian language skills that must be mastered by students of class XI SMA. An overview of the implementation of learning to write explanatory texts in high school forms the basis for the reflections of Indonesian language teachers. For this reason, this study aims to describe the implementation of teaching explanatory text writing skills in class XI SMA Negeri 2 Rejang Lebong. This study uses a qualitative approach with a descriptive method. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions. Test the validity of the data using data source triangulation. The results of the study showed that the implementation of Indonesian language learning on writing material for students of class XI IPS had been carried out in three stages: first, preliminary activities, the teacher greeted, greeted students, prepared students physically and psychologically, conducted apperception by way of question and answer and convey learning objectives. Second, the core learning activities, the teacher invites students to understand the meaning and characteristics of explanatory texts, identify knowledge information and explanatory text explanatory lines, analyze structure and language, and produce explanatory texts. Third, closing activities, the teacher concludes the learning material by involving students so that the teacher knows student understanding during the learning process. The learning steps carried out by the teacher are guided by the Learning Implementation Plan. Implementation of learning is planned to use discovery learning and project based learning models, but in the learning process, the implementation of these learning models is not maximized. The teacher's assessment was only a psychomotor assessment, while attitude and cognitive assessments were not carried out.